(untitled) (Ameghiniana, 2013)
Because of its stratigraphic peculiaritics and palcontological richness, the Santana Formation is distinct among the scdimentary units that make up the Mesozoic sequence of northeastem Brazil. To the already important amount of data on this formation, the author adds here the results of this Doctoral Thesis research. This paper comprises the first of four parts of this work. Presented in a concise way, are some geological considerations about the studied area and the systematic descriptions of thirty genera and fifty-eight species of spores of the Subturma Azonotriletes, of which one species is new.